More on stubs in open string field theory - Martin Schnabl; Georg Stettinger (Journal of High Energy Physics)
Abstract We continue our analysis of open string field theory based on A ∞ -algebras obtained from Witten’s theory by attaching stubs to the elementary vertex. Classical solutions of the new theory can be obtained from known analytic solutions in Witten’s theory by applying a cohomomorphism. In a previous work two such cohomomorphisms were found, one non-cyclic, obtained from the homological perturbation lemma and another one by geometric methods. Here we show that to first order in the stub length the two resulting maps are related by a combination of a gauge transformation and a term vanishing on-shell. We also extend our construction to more general gauges and explicitly calculate the first few orders of the new A ∞ -algebra solutions in the sliver frame.